Legal and social status of the child in contemporary Poland - MAJKOWSKI, WŁADYSŁAW (Prawo Kanoniczne, 2014)
One of the conditions that every society must fulfill in order to survive is the procreation and education of children as a replacement of generations and cultural continuity. In the first case, children fill the detriment to the population, which arises from the death of others, usually older people; in the second - cultural continuity is maintained - the child is socialized (raised) within the culture of his own society. This condition that society must meet to survive determines the rights of the child as part of a broader state legislation and ensure to the child the minimum necessary conditions in order to become a full-fledged citizen of his country and a member of a society that cares for it. Documents defining the rights of the child are of two levels: international and national. The former has been ratified by many countries and are thus binding on the forum of those countries. They are often complemented by State’s own legislation. A specific category of legislation is the Church’s legislation that protects the child in the specific way: it defines what kind of behavior is not allowed regarding the kids, for example, performing abortion. Moreover responsibilities towards the child are articulated in the analysis of moral norms. It happens often that articulated human rights of the child are not or at least not fully respected in a particular society. That means that the social objective situation of the child may significantly differ from the legal one.